Bionomics of the chironomidae of Barekese and Owabi reservoirs as a basis for formulating strategies for the control of the nuisance species - Amakye, Joseph Somua (2011)
A thesis submitted to the Department of Biological Sciences, College of Science, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Doctor Philosophy degree